Direito à moradia: uma antinomia entre a garantia do mínimo existencial e a cláusula da reserva do possível - Santos, Sabrina Zamana dos (2013)
The purpose of this dissertation is to check the opening of social rights in the Brazilian Federal Constitution, such as civil liberties that protect the less advantaged individuals, providing special attention to housing rights. The original Constitution text did not put the housing rights among the social rights. With the enactment of Constitutional Amendment No. 26/2000, the Article 6 of the Constitution was amended, and housing was included among those rights. Part of the doctrine, then, began to question the efficacy and effectiveness of housing rights understanding that, despite being formally constitutional, they are regulated by program standards and therefore can not be immediately required by the citizen. For these authors the housing rights are, necessarily, dependent on a positive activity of the State, which should create programs that are able to make them effective. Because the implementation of social rights require legal and material provisions by the Government, in many cases, it depends on the existence of budget resources, which is usually called reserve for contingencies. In this context, ensuring the minimum for the existence is a logical corollary of the human dignity principle, representing a minimum set of social, economic and cultural factors that may indeed be required from the State. However the Government has the duty to formulate and implement public policies, individuals often face the state inertia in promoting such minimum guarantee, which justifies the possibility of the Judiciary intervention.